Exercise‐induced endobronchial hemorrhage: a rare clinical presentation. Issue 4 (5th May 2016) - Kruavit, Anuk; Jain, Mukesh; Fielding, David; Heraganahally, Subash
Abstract: The phenomenon of exercise‐induced hemoptysis is still relatively underrecognised in humans. We report a case of recurrent hemoptysis brought on by vigorous exercise. A 33‐year‐old male presented with several episodes of intermittent fresh small‐volume hemoptysis reproducible on vigorous exercise. There was no other significant medical history other than a past history of testicular tumor, treated with orchidectomy and adjuvant Bleomycin‐based chemotherapy 1 year prior to onset of symptoms. Computed tomography scan showed no major abnormalities other than few small bilateral non‐specific nodules. Computed tomography aortogram and pulmonary angiogram, ventilation/perfusion scan, and echocardiography yielded no significant abnormalities. Infectious, autoimmune disease, coagulopathy, vasculitis, and malignant causes were excluded. Bronchoscopy showed possible endobronchial bleeding. This phenomenon is thought to be due to vulnerability of pulmonary capillaries to stress or mechanical failure during strenuous exercise at high cardiorespiratory workload. Abstract : The phenomenon of exercise induced haemoptysis is well‐known to occur in thoroughbred racehorses, but it is still relatively under‐recognised or reported in human subjects. A proposed mechanism is due to the alteration in the pulmonary capillary surface and collagen matrix structure in response to high transcapillary pressure during high cardiorespiratory workload. We report a case of recurrent frank endobronchial bleeding associated with vigorous exercise (jogging) in a patient previously treated with Bleomycin for testicular tumour.